Bermazhab dan Fanatik Mazhab: Satu Sorotan Dalam Kerangka Amalan Bermazhab Syafi'i Masyarakat Melayu - Hj Abdullah, Luqman; Jihatea, Nima (Jurnal Fiqh, 2007)
Generally, the Malay society in Malaysia has been practicing Shafi'ite mazhab since hundreds of years whether on taqlid or knowledge basis. This can be supported by the historical account of their daily practice, fatwas, laws and the curriculum at schools which show that the Shafi'ite mazhab has been dominating over the others. This article attempt to analyze this phenomenon based on two premises in the subject of Usul al-Fiqh, namely, al-tamadhub which is regarded as a necessity for certain level of people and madhabic fanatisme which is considered not in line with the Islamic principles. It is vital to determine that the prevalent Malay practice of madhab is in line with the concept of al tamadhub and not madhabic fanatisme.